Manipulation of Type I Interferon Signaling by HIV and AIDS-Associated Viruses - Buyuan He; James T. Tran; David Jesse Sanchez (Journal of Immunology Research)
Type I Interferons were first described for their profound antiviral abilities in cell culture and animal models, and later, they were translated into potent antiviral therapeutics. However, as additional studies into the function of Type I Interferons progressed, it was also seen that pathogenic viruses have coevolved to encode potent mechanisms allowing them to evade or suppress the impact of Type I Interferons on their replication. For chronic viral infections, such as HIV and many of the AIDS-associated viruses, including HTLV, HCV, KSHV, and EBV, the clinical efficacy of Type I Interferons is limited by these mechanisms. Here, we review some of the ways that HIV and AIDS-associated viruses thrive in Type I Interferon-rich environments via mechanisms that block the function of this important antiviral cytokine. Overall, a better understanding of these mechanisms creates avenues to better understand the innate immune response to these viruses as well as plan the development of antivirals that would allow the natural antiviral effect of Type I Interferons to manifest during these infections.